Evaluation of the technical and economic performances of shea mills and crushers in Benin - AHOUANSOU, ROGER H.; SEMASSOU, GUY CLARENCE; AGBOBATINKPO, BIDOSSESSI PÉLAGIE (My University, 2023)
Shea is a plant found in the central and northern regions of Benin. In the counties of Borgou and Alibori, for example, shea kernel provides basic cooking oil for more than 80% of the population. In recent years, the production of shea butter has emerged as a credible income generating activity alternative to the reduction in cotton income for the populations of northern Benin. It has become an important source of income to the women who are involved in collection and processing activities of shea kernel. This work is gradually witnessing the modernization of the sector by introducing new technologies to reduce the drudgery of butter extraction. Thus, the grinding (crushing) and milling operations have been mechanized, which allow labor reduction and time spent in the processing; and improve the profitability. However, in Benin, the technical and economic performance of the equipment introduced has not been documented. The study evaluated the technical and economic performance of crushers and mills of shea almonds. The technical performance of the machine is evaluated based on different parameters such as: throughput; broken rate; hourly consumption and specific consumption. The economic performance of the equipment focuses on costs and benefits, on indicators such as work times, variable costs, income and fixed costs, gross and net margins. The result obtained from the evaluation indicated that the throughput; broken rate; the crushing efficiency and gross margin of crusher BECRREMA type are respectively 501 kg/h; 100%; 98.8% and 925.32 FCFA/100 kg. The throughput; milling efficiency and gross margin of mill COBEMAG type are respectively: 62.95 kg/h; 99.5% and 2,412 FCFA/100 kg. These results show that these agro food equipment’s are efficient and cost-effective for the production of shea butter. Full dissemination of these improved technologies is recommended for development of shea processing sector in Benin and West Africa.
Keywords: Shea; throughput; milling efficiency; gross margin; fuel consumption.